Best friend - Stine, R. L. (New York Simon Pulse, 2002)
Who is Honey Perkins? She's been telling everyone in Shadyside that she's Becka Norwood's best friend. But Becka's sure she's never met Honey before.
"Originally published by Archway Paperbacks in December 1993"--Title page verso.
540L
106185
Keywords: Deception -- Juvenile fiction; Friendship; Fiction; Juvenile works; Horror fiction